ENT 530 Social Media Portfolio: Zakir Quran Pillow by Hajarkhalimi / Siti Hajar Mohd Khalimi - Mohd Khalimi, Siti Hajar (2021)
BabyPian is a trademark for our Zikir Pillow and Quran Pillow. The main objective for this product is to help children in developing innovative and creative technology for early childhood education. It offers variety of verses in the Quran, “Learning and Zikir” and collection of prayers to our customer with an affordable price. The business was developed in 2019 and officially launched on 31st January 2020. According to the customer review, both of our product which are Zikir Pillow and Quran Pillow, helps children a lot from being addicted to gadget. Not only that, this product is also very popular among parents due to its durability and travel friendly. Hence, this product provides a good vision for the continuation of sale to our customers. Since early of its launching, Zikir Pillow and Quran Pillow were sold more than 10,000 packages. The increasing demands of our product has resulted into a good profitable sale revenue to our business project. Therefore, Zikir Pillow and Quran Pillow by BabyPian is a good marketable product of choice that can be further expanded to many different areas as the business keeps on growing.